2022
DOI: 10.3389/fimmu.2022.972435
|View full text |Cite
|
Sign up to set email alerts
|

NKB cells: A double-edged sword against inflammatory diseases

Abstract: Interferon-γ (IFN-γ)-producing natural killer (NK) cells and innate lymphoid cells (ILCs) activate the adaptive system’s B and T cells in response to pathogenic invasion; however, how these cells are activated during infections is not yet fully understood. In recent years, a new lymphocyte population referred to as “natural killer-like B (NKB) cells”, expressing the characteristic markers of innate NK cells and adaptive B cells, has been identified in both the spleen and mesenteric lymph nodes during infectiou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Many studies have observed NKB cells to be enriched within various tissues, including the spleen and mucosae [ 1 , 3 , 9 ]. To rule out the potential nonspecific binding of antibodies, mononuclear cells from RM spleen were stained and analyzed by ImageStream cytometry.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Many studies have observed NKB cells to be enriched within various tissues, including the spleen and mucosae [ 1 , 3 , 9 ]. To rule out the potential nonspecific binding of antibodies, mononuclear cells from RM spleen were stained and analyzed by ImageStream cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…The rationale for choosing this method over more commonly used droplet-based methods (e.g. 10X Genomics) was three-fold: (i) the vastly improved signal in Smart-Seq allows for a high level of confidence to determine if a transcript is expressed or absent on a ‘per cell’ basis, and this resolution is not possible with droplet-based technology due to its inherently high drop-out level [ 3 ]; (ii) the rarity of NKB cells necessitates a high efficiency recovery method; and (iii) this approach allows for sequencing across the full-length of the transcript.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interferon-γ (IFN-γ), also called immune interferon, is an important cytokine present in the tumor microenvironment (TME). IFN-γ is mainly induced by mitogens or cytokines (such as IL-12 and IL-18), and is expressed in immune cells, especially T cells and natural killer (NK) cells 1 , 2 . IFN-γ binds to its receptors on the cell membrane, including the two subunits IFNGR1 and IFNGR2, forming a receptor complex that in turn activates the downstream JAK-STAT1 signal transduction pathway 3 and performs a series of biological functions.…”
Section: Introductionmentioning
confidence: 99%